2016
DOI: 10.1007/s00268-016-3848-8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between BMI and Recurrence of Primary Spontaneous Pneumothorax

Abstract: BackgroundWhether body mass index (BMI) is a significant risk factor for recurrence of primary spontaneous pneumothorax (PSP) remains controversial. The purpose of this study was to examine whether BMI and other factors are linked to risk of PSP recurrence.MethodsA consecutive cohort of 273 patients was retrospectively evaluated. Patients were divided into those who experienced recurrence (n = 81) and those who did not (n = 192), as well as into those who had low BMI (n = 75) and those who had normal or elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Low BMI is an established risk factors for the initial development of PSP [42,43]. While two studies demonstrated increased risk of recurrence with low weight and BMI, respectively, differing classifications precluded meta-analysis [5,6]. The hypothesis that PSP recurrence is linked with low body weight, either…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Low BMI is an established risk factors for the initial development of PSP [42,43]. While two studies demonstrated increased risk of recurrence with low weight and BMI, respectively, differing classifications precluded meta-analysis [5,6]. The hypothesis that PSP recurrence is linked with low body weight, either…”
Section: Discussionmentioning
confidence: 99%
“…Clinical study AL-ALAWI [17] AL-MOURGI [18] ANDERSEN [19] CASALI [10] CHAN [12] CHEN [20] CHEN [21] CHEN [22] GANESALINGAM [9] HARVEY [23] KARASAKI [25] KIM [26] KUAN [27] LICHTER [28] LIGHT [29] MARTÍNEZ-RAMOS [30] MEHTA [31] NISHIUMA [32] NOH [33] NOH [34] OLESEN [6] OUANES-BESBES [13] PRIMAVESI [8] SADIKOT [ due to nutritional deficiencies affecting α 1 -antitrypsin levels or due to unbalanced physical development, was supported by two papers [5,6,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations